Novel Innate Immune Genes Regulating the Macrophage Response to Gram Positive Bacteria. Issue 1 (1st September 2016) - Alper, Scott; Warg, Laura A; De Arras, Lesly; Flatley, Brenna R; Davidson, Elizabeth J; Adams, Jenni; Smith, Keith; Wohlford-Lenane, Christine L; McCray, Paul B; Pedersen, Brent S; Schwartz, David A; Yang, Ivana V
Abstract: Host variation in Toll-like receptors and other innate immune signaling molecules alters infection susceptibility. However, only a portion of the variability observed in the innate immune response is accounted for by known genes in these pathways. Thus, the identification of additional genes that regulate the response to Gram positive bacteria is warranted. Bone marrow-derived macrophages (BMMs) from 43 inbred mouse strains were stimulated with lipotechoic acid (LTA), a major component of the Gram positive bacterial cell wall. Concentrations of the proinflammatory cytokines IL-6, IL-12, and TNF-α were measured. In silico whole genome association (WGA) mapping was performed using cytokine responses followed by network analysis to prioritize candidate genes. To determine which candidate genes could be responsible for regulating the LTA response, candidate genes were inhibited using RNA interference (RNAi) and were overexpressed in RAW264.7 macrophages. BMMs from Bdkrb1-deficient mice were used to assess the effect of Bdkrb1 gene deletion on the response to LTA, heat-killed Streptococcus pneumonia e, and heat-killed Staphylococcus aureus . WGA mapping identified 117 loci: IL-6 analysis yielded 20 loci (average locus size = 0.133 Mb; 18 genes), IL-12 analysis produced 5 loci (0.201 Mb average; 7 genes), and TNF-α analysis yielded 92 loci (0.464 Mb average; 186 genes of which 46 were prioritized by network analysis). The follow-up small interfering RNA screen of 71 target genes identified four genes ( Bdkrb1, Blnk, Fbxo17, and Nkx6-1 ) whose inhibition resulted in significantly reduced cytokine production following LTA stimulation. Overexpression of these four genes resulted in significantly increased cytokine production in response to LTA. Bdkrb1-deficient macrophages were less responsive to LTA and heat-killed S. aureus, validating the genetic and RNAi approach to identify novel regulators of the response to LTA. We have identified four innate immune response genes that may contribute to Gram positive bacterial susceptibility.